Diversity of classic and novel human astrovirus in outpatient children with acute gastroenteritis in Shanghai, China - Lu, Lijuan; Zhong, Huaqing; Xu, Menghua; Jia, Ran; Liu, Pengcheng; Su, Liyun; Cao, Lingfeng; Zhu, Xunhua; Xu, Jin (Frontiers in Microbiology, 2023)
Introduction Human astrovirus (HAstV) is an important pathogen of acute gastroenteritis (AGE) in children. This study was aimed at investigating the diversity and epidemiology of classic and novel HAstV in outpatient children aged 0–16 years old with AGE in Shanghai. Methods From May 2020 to December 2022, a total of 1,482 stool samples were collected from children diagnosed as AGE from the Children’s Hospital of Fudan University. HAstV was identified using pan-astrovirus consensus primers by Reverse transcription PCR. Results During the study period, 3.3% (49/1,482) of specimens were identified as HAstV, with a detection rate of 2.5% (37/1,482) for classic HAstV and 0.8% (12/1,482) for novel HAstV. Among the 12 novel HAstV strains, 11 (91.7%) belonged to the HAstV-MLB and 1 (8.3%) was HAstV-VA. Genotyping revealed six circulating genotypes. Strain HAstV-1 was predominant in the study population with a detection rate of 1.8% (26/1,482) followed by HAstV-MLB1 (0.7%, 10/1,482) and HAstV-4 (0.6%, 9/1,482). Of note, all the HAstV-4 strains detected in this study were close to one astrovirus strain isolated from Bactrian camels with 99.0-100.0% amino acid sequences identity. In this study, HAstV was detected in all age groups with the highest detection rate of HAstV-positive specimens observed in children older than 73 months (5.7%, 12/209). Discussion This study provided useful information and contributed to the molecular epidemiology of both classic and novel HAstV, which were simultaneously characterized and reported for the first time in Shanghai.